CHAIN RELATION IN A FAMILY OF SETS. CHAIN FUNCTION - Misajleski, Zoran; Durmishi, Emin (Matematichki Bilten, 2025)
In this paper we define connectedness of a family of sets, by defining the terms finite chain in the family and chain relation between two sets. Furthermore, we define a chain function between two families of sets. Some properties of connected families and chain functions are obtained.